Feasibility Study of Wafer Scale Laser Assisted Thermal Imprinting of Glass Nanostructures - Lee, Helen; Syarifah Nur Hasanah, Syed Kamarudin; Ismayuzri, Ishak; Ahmad Rosli, Abdul Manaf; Ahmad Shahir, Jamaludin; Mohd Ali Hanafiah, Shaharudin; Mohd Zairulnizam, Mohd Zawawi (Springer, Singapore, 2021)
Major challenges for any direct nanostructuring method on glass substrate is the difficulty to scale up the patterning area to industrial scale. In this work, a rapid and large area direct thermal imprinting of glass nanostructures using silicon mold assisted by CO2 laser irradiation was demonstrated. Pattern transfer was successful for experiment trial of one spot laser irradiation and laser scanning with imprinting area of 100 mm2 and 400 mm2; confirmed by SEM and AFM measurement. When the method was extended to a larger imprinting area (2000 mm2), the glass was cracked and partially imprinted due to the high cooling rate of the glass after laser irradiation and misalignment of the glass during the contact pressing step in our molding setup.